DETERMINAN UNDERPRICING SAHAM SAAT IPO PADA BURSA EFEK INDONESIA PERIODE 2017-2019 - Clarisya Munajat, (2020)
This research is using quantitative study aimed to see wheter there are influence of Underwriter's Reputation, Type of Industry, Return on Equity (ROE), and Inflation to Underpricing of Shares. The sampling method in this study uses probabilty sampling method. The sample used in this study were 138 companies that conducted to IPO and Underpricing. The type of data used is secondary data. Testing the hypothesis in this study was used Multiple Linear Regression Analysis using SPSS version 24. This resesarch shows that Underwriter's Reputation has a negative influence on Underpricing, otherwise Type of Industry, Return on Equity (ROE), and Inflation has no influence to Underpricing of Shares.